Ovid's Homer : authority, repetition, reception - Boyd, Barbara Weiden (Oxford University Press, 2017)
This work examines the Latin poet's engagement with the Homeric poems throughout his career. Boyd offers detailed analysis of Ovid's reading and reinterpretation of a range of Homeric episodes and characters from both poems, and demonstrates the pervasive presence of Homer in Ovid's work